Emergence of Haemophilus influenzae with low susceptibility to quinolones isolated from pediatric patients in Japan. Issue 7 (July 2021) - Takeuchi, Noriko; Ohkusu, Misako; Hoshino, Tadashi; Yamamoto, Shota; Segawa, Shunsuke; Murata, Shota; Ishiwada, Naruhiko
Abstract: Introduction: In 2010, oral fluoroquinolone tosufloxacin (TFX) granules were released as the first oral respiratory quinolone for children in Japan. Methods: To investigate the recent trend of H. influenzae strains with low susceptibility to quinolones in children, we analyzed the gene sequences of quinolone resistance-determining regions (QRDRs) of gyrA, gyrB, parC, and parE of 23 clinical isolates from 15 patients aged <15 years with an MIC of ≥0.5 μg/mL for TFX from 2010 to 2018. Results: Amino acid substitutions were observed in both GyrA and ParC in 13 strains (81%, 13/16), except two strains with a TFX MIC of 0.5 μg/mL with amino acid substitution in only GyrA and one strain with a TFX MIC of 1 μg/mL with no amino acid substitution. Four ST422 strains were observed in 2018, the detection age range was wide (0–7 years), and the residential city was varied. A total of 3/15 patients had a clear history of TFX treatment. Conclusions: Even for the strain with an MIC of 0.5 μg/mL for TFX, it is highly possible that it harbors a mutation in gyrA, which is the first step toward quinolone resistance, and it may also harbor mutations in both gyrA and parC . Furthermore, several specific sequence type quinolone-resistant H. influenzae strains, particularly ST422, may be widespread among children in Japan. It is necessary to investigate changes in resistance both at the MIC and gene levels. The continuous monitoring of strains and the use of antimicrobial drugs in treatment should be carefully observed.